Characterisation of Plasmodium invasive organelles; an ookinete microneme proteome. - Lal, K; Prieto, J; Bromley, E; Sanderson, S; Yates, JR; Wastling, J; Tomley, F; Sinden, R (2009)
Secretion of microneme proteins is essential to Plasmodium invasion but the molecular composition of these secretory organelles remains poorly defined. Here, we describe the first Plasmodium microneme proteome. Purification of micronemes by subcellular fractionation from cultured ookinetes was confirmed by enrichment of known micronemal proteins and electron microscopy. Quantitation of electron micrographs showed >14-fold microneme enrichment compared to the intact ookinete, such that micronemes comprised 85% of the identifiable organelles in the fraction. Gel LC-MS/MS of the most abundant protein constituents of the fraction identified three known micronemal proteins chitinase, CTRP, SOAP, together with protein disulphide isomerase (PDI) and HSP70. Highly sensitive MudPIT shotgun proteomics described a total of 345 proteins in the fraction. M1 aminopeptidase and PDI, the former a recognised target of drug development, were both shown to have a micronemal location by IFA. We further identified numerous proteins with established vesicle trafficking and signaling functions consistent with micronemes being part of a regulated secretory pathway. Previously uncharacterised proteins comprise the largest functional group of the microneme proteome and will include secreted proteins important to invasion.